THE USE OF CAPOEIRA AS A CLINICAL DEVICE WITH PSYCHOTIC PATIENTS IN A PSYCHOSOCIAL CARE CENTER (CAPS II) - Nunes de Carvalho Júnior, Antônio Carlos; Matos do Amparo, Deise (Brazilian Journal of Mental Health, 2022)
This research studies the process of primary symbolization in psychotic patients. The main purpose of this work is to examine the impacts of therapeutic mediation in the clinic of psychosis through the analyses of the therapeutic activity of capoeira in a Psychosocial Care Center (CAPS II). We discuss the thesis that the therapeutic mediation promoted by the use of capoeira as a clinical tool enables the processes of primary symbolization in psychotic individuals. Data was extracted from this therapeutic activity through the use of field diaries (by the researcher and research auxiliaries from an extension project of the University of Brasilia - UnB) and systematized. We conclude that the use of capoeira as a tool of mediation in the clinical work of the CAPS promotes aspects that facilitate the primary symbolization processes with psychotic individuals. These aspects can be grouped in three fundamental fields relating to: creativity, movement and rhythm; environment and settings that hold and promote play and a playful experience through games, group dynamics and the roda of capoeira; the organization of the group and the rituals, which relate to the Oedipal Complex and the construction of representations and fantasies.